Renal Tubular Epithelial Vacuoles—A Marker for Both Hyperlipidemia and Ketoacidosis at Autopsy. Issue 3 (12th February 2015) - Zhou, Chong; Moore, Lynette; Yool, Andrea; Jaunzems, Alvis; Byard, Roger W.
Abstract Review of 15 cases of nephrotic syndrome found that eight had significant hyperlipidemia with serum cholesterol levels ranging between 10.59 and 18.60 mmol/L (mean 12.88) and serum triglyceride levels between 2.30 and 9.92 mmol/L (mean 4.58); all of these cases displayed basal lipid vacuolization. Seven of the 15 study cases had normal–mild hyperlipidemia with serum cholesterol levels ranging between 4.71 and 7.54 mmol/L (mean 6.02) and serum triglyceride levels between 0.65 and 4.1 mmol/L (mean 1.57). Six of the seven cases had basal lipid vacuoles (86%). Of these, five cases were hyperlipidemic and one case had borderline hyperlipidemia with a serum cholesterol level of 4.71 mmol/L. Although hyperlipidemia was associated with renal tubular epithelial vacuolization, the vacuoles appeared morphologically different to those found in ketoacidosis. This study has shown that while hyperlipidemia in isolation may result in basal lipid vacuolization within renal tubular epithelial cells, the phenotype differs from that observed in ketoacidosis.